TEPT, suporte social e regulação emocional em profissionais que atuaram no incêndio da boate Kiss - Barbosa, Luciana Dantas Figueiredo (2018)
Many health and emergency professionals are involved in the aftermath of community disasters,taking care of victims and being exposed directly and indirectly to traumatic events. These professionalsare at risk of developing posttraumatic stress symptoms. In Brazil, one of the most striking community tragedies was the fire at the Kiss nightclub, which took place in the city of Santa Maria - RS, at the dawn of January 27th, 2013. In this sense, this dissertation is composed of two empirical studies presented in the form of articles. The objective of this study is to explore the relationship between PTSD, social support and emotional regulation strategies in health and emergency professionals who assisted the victims of the Kiss Nightclub fire, as well as to describe the experience of the professionals who participated in this event. The first article is a quantitative study with a cross-sectional, correlational design. The sampling process was non-probabilistic by convenience, and the sample consisted of 99 health and emergency professionals from the Santa Maria public and private sectors, who consented to participate in the study. The instruments used were: sociodemographic questionnaire, Post Traumatic Cognitions Inventory, The Life Events Checklist for DSM-5, PTSD Checklist, Social Support Perception Scale, and the Cognitive Emotional Regulation Questionnaire. The data were analyzed in the Statistical Package for Social Sciences 17.0 (SPSS). The results pointed out that low social support and maladaptive emotion regulation strategies are positively correlated with posttraumatic stress symptoms, and that posttraumatic cognitions predict posttraumatic symptoms. The second article is an exploratory cross-sectional study structured with a qualitative approach. Data collection was carried out in the workplaces of the health and emergency professionals of Santa Maria - RS, by the team of researchers. Collection consisted of an interview with a sample of five participants who were selected from the first study, by the criterion of presenting higher PTSD symptom scores. A topic interview script was used which included questions related to the context of the tragedy, immediate impacts, long term effects and meanings that the professionals gave to the experience of attending to the victims. A Theme Analysis was conducted, as proposed by Braun e Clarke (2006). The study shows that, even five years past this tragedy, health professionals continue to suffer with posttraumatic stress symptoms, such as avoidance and hypervigilance, and have used coping resources, task focus, social support and spirituality. As for meanings, some interpret the situation as a tragedy and a scar in the lives of the people involved and in the community; others understand that the event has provided professional growth and changes in the security protocols of enclosed spaces. This dissertation aimed at promoting advances in the literature on PTSD in health and emergency professionals in situations of community tragedies, contributing to increase the knowledge about PTSD prevalence in this population and associated factors. In addition, the understanding of the context, impacts and meanings that the professionals gave to their experience in the tragedy of Santa Maria aid in understanding the psychological consequences of the work with people exposed to traumas. This could guide the development of interventions for the promotion of health and wellbeing of such professionals.